2015
DOI: 10.3126/jpahs.v1i1.13013
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from Laparoscopic to Open Cholecystectomy

Abstract: Introductions: With the advent of newer technology, the era of open surgery for gall bladder diseases has been preferably taken over by laparoscopic cholecystectomy. However, certain cases still require conversion to open surgery. In this review we aim to analyze the reason for conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
2
1
Order By: Relevance
“…Open method still common procedure done for our patients in current study this is probably due to lack in instruments and in some to low experience. This agree with Shrestha et al (2014) study, who also reported several possible factors responsible for this conversion. These include age, sex, obesity, diabetes mellitus, acute cholecystitis, history of biliary diseases such as jaundice, cholangitis, history of pancreatitis (Shrestha et al 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Open method still common procedure done for our patients in current study this is probably due to lack in instruments and in some to low experience. This agree with Shrestha et al (2014) study, who also reported several possible factors responsible for this conversion. These include age, sex, obesity, diabetes mellitus, acute cholecystitis, history of biliary diseases such as jaundice, cholangitis, history of pancreatitis (Shrestha et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Laparoscopic and open cholecystectomy were used for our patients in this study, with a conversion from laparoscopic to open procedure at a rate of 2.5%. this was less than the rate in Shrestha et al (2014) study where it was (11.1%), and less than the conversion rate of Pimpale et al (2014) study (6.57%).…”
Section: Discussioncontrasting
confidence: 58%
“…In this study, difficult laparoscopic cholecystectomy confronted the surgical team in 137 patients (33.8%), which is similar to what were reported by Atta H et al (32%) [7], Mudgal M (34%) [15], as well as Singh K et al (34%) [22], and located between the two extreme ratios which were mentioned by Nidoni R et al (24.4%) [17],and Verma D et al (46%) [29]. The study showed conversion rate of 6.4%, which compares well with the incidence reported in the literature, which varies from 2-15% [6,17,21,22,23].…”
Section: Discussionsupporting
confidence: 79%
“…Kumar A et al (1996) 13 14.3%. 4 Samir shrestha et al (2014) 14 11.14 %. Conversion rate (8.85%) is comparable with other studies whereas conversion rate in difficult cases (26.58%) is slightly higher in our study which is considerable on the basis of fact that this is an institutional study.…”
Section: Operative Timementioning
confidence: 98%